(untitled) (Damascus University Journal for engineering sciences, 2022)
A Wireless Body Area Network (WBAN) is a group of communicating wireless sensors that exchange biological values measured from a human body. This network is used essentially in health care systems. In such systems, security attacks on the exchanged biological data have negative effect and may threaten patient’s life. Therefore, maintaining the confidentiality and integrity of health information in WBAN is a very essential requirement. The generation of random bit sequences (RBSs) is an essential aspect of protecting WBAN. However, due to the very limited resources of these networks, traditional pseudorandom number generators cannot be used as they consume a lot of energy and processing power. To reduce resource consumption in WBANs, some researchers suggested using biometrics ​​in generating random bit sequences, specifically the electrocardiogram (ECG) signal. Nevertheless, their methods suffer from low throughput that is inconsistent with healthcare applications in real time. In this paper, we present a new random sequence generator based on ECG signal, which has a throughput tens or hundreds of times higher than previous methods. In addition, the developed generator reduces resources consumption due to its very simple processing operations. To evaluate the proposed generator, RBSs of 128 bits were generated from two ECG data sets, the first is for healthy people, and the second is for people who suffer from arrhythmia. Randomness and distinctiveness of generated RBSs are measured by using the National Institute of Standards and Technology (NIST) statistical tests and hamming distance. Thus, we have proved that the resulting RBSs are appropriate for information security applications.